Assessing Knowledge, Attitudes, and Practices of Healthcare Workers regarding Biomedical Waste Management at Biyem-Assi District Hospital, Yaounde: A Cross-Sectional Analytical Study - Sylvain Honoré Woromogo; Gwladys Guetsé Djeukang; Félicité Emma Yagata Moussa; Jesse Saint Saba Antaon; Kingsley Ngah Kort; Pierre Marie Tebeu (Advances in Public Health)
Background. Biomedical waste (BMW) is defined as unwanted materials generated during diagnosis, treatment, operation, immunization, or in research activities including production of biologicals. Healthcare workers are responsible for the proper management of this waste for human safety and for the protection of the environment. Methods. An analytical knowledge, attitude, and practice (KAP) study was carried out at Biyem-Assi District Hospital from June 1st to July 5th, 2018, including 100 health workers from different departments. Variables of interest were knowledge, attitudes, and practices of the respondents. A structured and pretested questionnaire was used for data collection. Data analysis was carried out using software Epi Info version 7.2.2.6. Logistic regression was used to establish the relationship between knowledge, attitudes, and practices. Results. Nurses constituted 32.0% of the participants, and more than half of the participants had 1–4 years of working experience (56.0%). Overall, the level of knowledge was satisfactory at 50.0%, that of attitudes was as unfavorable at 83.0%, and that of practices was as poor at 50.0%. Favorable attitudes were associated to satisfactory level of knowledge (ORa = 5.14 [3.10–8.51] and p=0.005). Good practices were associated to good level of knowledge (ORa = 5.26 [3.17–8.7] and p<0.001) and a favorable attitude (ORa = 7.30 [2.25–23, 71] and p<0.001). Conclusion. The level of knowledge was considered unsatisfactory for half of the staff interviewed. Attitudes were unfavourable at 83.0% and poor practices at 50.0%. Staff with a good level of knowledge were more likely to have favourable attitudes towards BWM. Also, good knowledge and attitude positively influenced the practice with regard to BMW management.